2022
DOI: 10.1007/s40670-022-01674-y
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of Student Resource Use and Academic Performance in Preclerkship Education: A Survey Study

Abstract: Medical students have unprecedented access to a large variety of learning resources, but patterns of resource use, differences in use across education cohorts, and the relationship between resource use and academic performance are unclear. Therefore, the purpose of the current study was to evaluate student resource use and its relationship to academic performance during preclerkship years. First-year and second-year medical students completed a 10-question electronic survey that assessed likelihood of using ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Ikonne U et al found a statistically significant positive correlation between usage of review resources and academic performance in the case of both first- and second-year medical students. However, the correlation was not studied in relation to the number of resources [ 16 ]. Bauzon, J et al found that higher exam scores were moderately associated with less utilization of commercial review resources [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Ikonne U et al found a statistically significant positive correlation between usage of review resources and academic performance in the case of both first- and second-year medical students. However, the correlation was not studied in relation to the number of resources [ 16 ]. Bauzon, J et al found that higher exam scores were moderately associated with less utilization of commercial review resources [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Ikonne U et al from Eastern Virginia Medical School found that students started using review resources from the first year. The authors recommend designing learning sessions and curricula to accommodate review resources to make students effective self-regulated learners [ 16 ]. Makus D et al from the University of Ottawa suggest restructuring curriculum design and delivery in order to make room for nontraditional learning resources in the official curriculum [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation